Daughter and mother diagnosed with hereditary multiple exostoses: A case report and a review of the literature - Mărginean, Cristina Oana (Medicine (Baltimore), 2017)
INTRODUCTION: Hereditary multiple exostoses (HME) or osteochondromatosis is a rare autosomal dominant disease characterized by multiple osteochondromas and skeletal deformities. PATIENT CONCERNS & DIAGNOSES: We present the case of a 5 years and 9 month-old patient who presented with inferior limb pain for approximately 6 months, associating also deformity of the right index finger for a month. Hand X-ray revealed a radiologic abnormality of the right radius, therefore the child was referred to our clinic for further investigations. The X-rays revealed multiple osteochondromas of the radius, metacarpal bones, hand phalangeal bones, femur, tibia, fibula, metatarsal bones, and foot phalangeal bones. We mention that the same radiological aspect was identified in the case of the patient's mother, undiagnosed until that moment. OUTCOMES: The particularity of this case consists in identification of a rare genetic pathology, HME in a 5-year-old patient, without any known familial history, after the occurrence of a nontraumatic joint dislocation of the right index finger. CONCLUSION: HME is a rare genetic condition, without a curative treatment, burdened by multiple complications, and whose diagnosis is usually established during childhood.